2006
DOI: 10.1001/archfaci.8.4.260
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Concurrent Rhinoplasty and Sinus Surgery

Abstract: To evaluate the safety and efficiency of and patient satisfaction with a 2-team approach for combined rhinoplasty and sinus surgery.Methods: Weconductedaretrospectivemedicalchartanalysis of consecutive patients with sinus disease and functional nasal obstruction. Forty-four patients (29 women and 15 men; age range, 22-75 years) had severe nasal obstruction with chronic sinusitis and were found to have indications for this procedure. All patients were followed up for a minimum of 6 months after surgery. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…While these authors did not describe the extent or findings of the sinus surgery, they did note that they did not perform concurrent CR on any patient with preoperative CT evidence of severe (defined as Lund‐Mackay score of 8 or more) sinusitis. Finally, Marcus et al9 reported only 2 of 44 patients who underwent concurrent ESS/CR over an 8‐year period developed postoperative cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…While these authors did not describe the extent or findings of the sinus surgery, they did note that they did not perform concurrent CR on any patient with preoperative CT evidence of severe (defined as Lund‐Mackay score of 8 or more) sinusitis. Finally, Marcus et al9 reported only 2 of 44 patients who underwent concurrent ESS/CR over an 8‐year period developed postoperative cellulitis.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the combined procedure was safe, but patients should be screened for woundhealing factors as well as severe sinusitis. Marcus et al 17 also reported on 44 patients undergoing concurrent FESS and SRP. In addition to reporting only 2 complications, 1 cellulitis (2.3%) and 1 vestibulitis (2.3%), they carried out a patient satisfaction survey and reported that 92% of patients said they would recommend a concurrent procedure to others.…”
Section: Resultsmentioning
confidence: 99%
“…However, with the advent of minimally invasive techniques for performing FESS, there is less disruption to nasal structures that support the external nose. Moreover, with present perioperative antibiotic therapy, contamination of the external nose from sinusitis is low . Several authors suggest that if surgery is indicated, a combined procedure seems to offer the benefit of reduced healing time, decreased cost, and increased operative efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with present perioperative antibiotic therapy, contamination of the external nose from sinusitis is low . Several authors suggest that if surgery is indicated, a combined procedure seems to offer the benefit of reduced healing time, decreased cost, and increased operative efficiency . However, a recent review of the literature on the combination of these two procedures provides evidence from single‐surgeon/single‐institution case series only .…”
Section: Introductionmentioning
confidence: 99%